Effect of yield stress on fatigue crack growth - M.F. Borges; F.V. Antunes; P. Prates; R. Branco; M.C. Oliveira (Fracture and Structural Integrity)
Fatigue crack growth (FCG) depends on loading, geometry and also material properties. Since FCG is supposedly linked to crack tip plastic deformation, materials yield stress, Y0, is an important parameter. The main objective here is to develop a parametric study focused on the effect of Y0 on FCG. The study is based on the plastic CTOD, (p, determined numerically using the finite element method. The increase of Y0 was found to decrease (p, and therefore FCG rate. The variation is non-linear, being more important for lower values of Y0. The effect of Y0 was found to be much more relevant for the 7050 aluminium alloy than for the 304L stainless steel, which indicated a major influence of isotropic saturation stress. With the inclusion of crack closure, the reduction of (p is kept, but there is a substantial reduction of (p and therefore of FCG rate.